Wide versus narrow excision margins for high-risk, primary cutaneous melanomas: long-term follow-up of survival in a randomised trial. Issue 2 (February 2016) - Hayes, Andrew J; Maynard, Lauren; Coombes, Gillian; Newton-Bishop, Julia; Timmons, Michael; Cook, Martin; Theaker, Jeffrey; Bliss, Judith M; Thomas, J Meirion; ,; ,; ,
Summary: Background: The necessary margin of excision for cutaneous melanomas greater than 2 mm in thickness is controversial. At a median follow-up of 5 years, findings from our previously published randomised trial of narrow (1 cm) versus wide (3 cm) excision margins in patients with thick cutaneous melanomas showed that narrow margins were associated with an increased frequency of locoregional relapse, but no significant difference in overall survival was apparent. We now report a long-term survival analysis of that trial. Methods: We did a randomised, open-label multicentre trial in 59 hospitals—57 in the UK, one in Poland, and one in South Africa. Patients with one primary localised cutaneous melanoma greater than 2 mm in Breslow thickness on the trunk or limbs (excluding palms or soles) were randomly assigned (1:1) centrally to receive surgery with either a 1 cm or 3 cm excision margin following an initial surgery. The randomisation lists were generated with random permuted blocks and stratified by centre and extent of initial surgery. The endpoints of this analysis were overall survival and melanoma-specific survival. Analyses were done in the intention-to-treat population. This trial was not registered because it predated mandatory trial registration. Findings: Between Dec 16, 1992, and May 22, 2001, we randomly assigned 900 patients to surgery with either a 1 cm excision margin (n=453) or a 3 cm excision margin (n=447). At a median follow-up of 8·8 years (106 months [IQR 76–135], 494 patients had died, with 359 of these deaths attributed to melanoma. 194 deaths were attributed to melanoma in the 1 cm group compared with 165 in the 3 cm group (unadjusted hazard ratio [HR] 1·24 [95% CI 1·01–1·53]; p=0·041). Although a higher number of deaths overall occurred in the 1 cm group compared with the 3 cm group (253 vs 241), the difference was not significant (unadjusted HR 1·14 [95% CI 0·96–1·36]; p=0·14). Surgical complications were reported in 35 (8%) patients in the 1 cm excision margin group and 65 (15%) patients in the 3 cm group. Interpretation: Our findings suggest that a 1 cm excision margin is inadequate for cutaneous melanoma with Breslow thickness greater than 2 mm on the trunk and limbs. Current guidelines advise a 2 cm margin for melanomas greater than 2 mm in thickness but only a 1 cm margin for thinner melanomas. The adequacy of a 1 cm margin for thinner melanomas with poor prognostic features should be addressed in future randomised studies. Funding: Cancer Research UK, North Thames National Health Service Executive, Northern and Yorkshire National Health Service Executive, British United Provident Association Foundation, British Association of Plastic Surgeons, the Meirion Thomas Cancer Research Fund, and the National Institute for Health and Research Biomedical Research Centre at The Royal Marsden NHS Foundation Trust.